The Holiness composition in the Book of Exodus - Tucker, Paavo N. (Forschungen zum Alten Testament / 2, 2017)
Publisher's description: In this study, Paavo N. Tucker investigates different models of the formation of the Priestly literature in the Pentateuch by analyzing the relationship between the Priestly narratives in the Book of Exodus and the laws of the Holiness Code in Lev 17-26